Tentative Program for the California State Democratic Convention (1968)
This document outlines the tentative program for the California Democratic State Convention on August 10, 1968, and the California Democratic State Central Committee meeting on August 11, 1968. The convention agenda includes committee appointments, remarks and addresses by prominent Democratic leaders such as Alan Cranston, Eugene McCarthy, and Vice President Hubert H. Humphrey, as well as the nomination of presidential electors and adoption of a state platform. It explains the composition of the convention, including nominee, holdover, and appointive delegates as defined by the California Election Code. The document also details the structure, purpose, and membership of the State Central Committee, identifying it as the official governing body of the California Democratic Party. Finally, it describes procedural rules for meetings, officer elections, executive committee selection, terms of office, and quorum requirements.